Nanotechnological Approaches to the Advancement of Innovations in Aquaculture - Kirthi, A Vishnu; Loganathan, Karthik; Karunasagar, Iddya (Cham : Springer International Publishing : Imprint: Springer, 2023)
The main practical breakthrough of this century is nanobiotechnology, an amalgamation of biology and nanotechnology based on the standards and methods of metabolism. The field mainly involves the analysis, synthesis and the links between molecular biology, nutritional science and nanotechnology. In addition, the field involves the links between other life sciences branches, since the improvement of nanotechnology strategies might be directed by considering the structure and the capability of nanoparticles present in the living cells. This book is a comprehensive evaluation of the latest nanobiotechnological developments, with an emphasis on applications, especially in aquaculture. It outlines, in-depth, modern techniques, and includes a variety of important sources that make this the perfect resource for researchers in this captivating world of nanobiotechnology.
Preface -- Simple Basics of Aquaculture Nanosciences Research -- Current Nanotechnology Developments in the Aquaculture Industry -- Aquatic Nanodrug Delivery -- Nanosensors Used in Aquaculture -- Alarming Viral Pathogens in Shrimp Industry and Nanotechnology -- Bioenrichment of Planktons in Aquaculture through Nanotechnological Approaches -- Water Purification and Bioremediation Nanotechnologies -- The Challenge of Nanotechnology-Derived Food -- Nanoengineered Particles in Seafood -- Harvested Fish Management and Commercialization Packaging -- Nanotechnologies in Aquaculture Health Issues -- Bibliography -- Index.
Keywords: Plant biotechnology; Nanobiotechnology; Microbiology; Plant Biotechnology; Nanobiotechnology; Microbiology